The Contribution Of Universal Education Towards Girl Child Education: A Case Study Of Nyarubuye Sub-County Kisoro District. - Nizeyimana, Bakunzi Moses (Kabale University, 2024)
The findings of the study research report focused on the contribution of universal education to girl child education in Nyarubuye sub-county, Kisoro district. The study's objectives were to examine how universal education has contributed to promoting girl child education, identify barriers to universal education's promotion of girl child education, and identify potential solutions to these barriers. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on universal education as an independent variable and sustainable girl-child education as a dependent variable. The methodology of the study employed a descriptive research design, where the methods of data collection were put into action. The research used both qualitative and quantitative methods of data collection and analysis. The study collected and analyzed data using simple random sampling techniques and was designed to give each of the 55 respondents an equal chance. Purposive sampling was also used to collect data from respondents who participated in the study. The study's findings were obtained from the field by interpreting and analyzing the results based on the study's specific objectives. The findings of the study revealed that Universal Education has contributed much towards girl child education through the elimination of school fees, creation of other enabling education programs, promotion of gender sensitivity, increased enrollment rates in classes, female literacy, and improved girls' access to education. The majority of respondents agreed that class enrollment had increased. The study concluded that although universal education policy had achieved much in terms of access and retention of school-age pupils in primary schools in Nyarubuye sub-county in Kisoro District, it had, on the contrary, compromised the quality of education not only in Nyarubuye sub-county but in Uganda as a country at large. This has been proved by the ever-increasing poor performance of most pupils in the Primary Leaving Examinations (PLE), where very few schools managed to score a grade I pass. Several factors have been attributed to this poor phenomenon in education, including poor funding of the UPE program, high teacher-to-pupil ratios, and a lack of scholastic materials. Furthermore, teachers, who are key players in the implementation of the curriculum, are not motivated to work hard and mobilize more girls to be in school.